1967
DOI: 10.1111/j.1476-5381.1967.tb02132.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chlorpromazine and Thioridazine on the Exploration of a Y‐maze by Rats

Abstract: When a rodent is put into a situation with which it is unfamiliar, exploratory behaviour is elicited and the animal investigates the surroundings. In exploration, all the animal's sense organs are used to receive stimuli from the unfamiliar area and generally it moves through the area to increase the range of available stimuli. Many workers have used this movement as a measure of exploratory behaviour in the animal, and in particular Steinberg, Rushton & Tinson (1961), , Rushton, Steinberg & Tinson (1963) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1968
1968
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Steinberg et al (1) showed that the naive rats explored relatively little at the first trial, but the number of entries to the arms of the box gradually increased in the successive trials. On the other hand, the gradual decrease in the number of entries caused by the repetition of the regular trials was reported by Mar riott and Spencer (4) and Schillito (7). In the present experiments the locomotion and rearing frequencies were relatively stable from the first to sixth trial in the Wistar strain rats and from second to sixth trial in the Sprague-Dawley strain rats.…”
Section: Discussionsupporting
confidence: 59%
“…Steinberg et al (1) showed that the naive rats explored relatively little at the first trial, but the number of entries to the arms of the box gradually increased in the successive trials. On the other hand, the gradual decrease in the number of entries caused by the repetition of the regular trials was reported by Mar riott and Spencer (4) and Schillito (7). In the present experiments the locomotion and rearing frequencies were relatively stable from the first to sixth trial in the Wistar strain rats and from second to sixth trial in the Sprague-Dawley strain rats.…”
Section: Discussionsupporting
confidence: 59%
“…This can be seen when a mouse or rat is put in the same situation on two successive days, or even with some longer time interval between trials. Normal rats behave differently on two successive trials in a Y-maze as they move much less on the second trial (Shillito, 1967). Rushton, Steinberg & Tinson (1963) and Rushton, Steinberg & Tomkiewicz (1968) have found more complicated changes in behaviour which they attribute to an interaction between maze experience and drugs.…”
Section: Discussionmentioning
confidence: 99%
“…This movement has been used as a basis for measuring the effects of drugs on " exploratory " behaviour, a category of behaviour which gives the animal information about its environment. The effects of drugs on the movement of rats in a Y-maze were first studied by Rushton, Steinberg & Tinson (1961) and have also been used by Marriott & Spencer (1965), Shillito (1967) and others. Changes in the behaviour of mice as a result of drug treatment on a square board with regularly spaced holes in it have been studied by Boissier & Simon (1964) and Joyce, Porsolt, Steinberg & Summerfield (1968).…”
Section: Introductionmentioning
confidence: 99%
“…This response is indicative of retention and transfer of some experience from the first day. Shillito (1967) suggests that the decrease in movement observed on the second day can be taken to demonstrate that learning has taken place. The rats given the extract did not show significant habituation.…”
Section: Discussionmentioning
confidence: 95%
“…The other end of the arm at the centre was open to allow for movement from one arm into another. The three arms were made as similar as possible to prevent preference on the part of the animal when introduced into the maze (Shillito, 1967).…”
Section: The Mazementioning
confidence: 99%